Impact of nutrition education on maternal hemoglobin and calcium levels during pregnancy and their association with birthweight in an Indian cohort - Khan, M. Faisal; Khurana, Ashok; Sharma, K. Aparna; Nigam, Aruna; Alam, Sana; Idris, M. Ghaznavi; Dev, Kapil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Maternal nutrition during pregnancy is pivotal for fetal growth, neonatal health, iron stores across infancy and adolescence, and future adult disease risk. In India, this role is especially important because anemia, micronutrient deficiencies, and protein-energy malnutrition remain widespread despite national supplementation programmes. Many women still experience suboptimal outcomes due to poor dietary diversity and inconsistent adherence to iron, calcium, and protein recommendations. This study examined the effect of trimester-specific nutrition education on maternal hemoglobin and calcium levels during pregnancy. It examined whether these changes were associated with birth weight in an Indian cohort. Methods: A prospective quasi-experimental cohort study was conducted at a tertiary care hospital in New Delhi among 200 pregnant women, systematically allocated to an intervention group receiving structured nutrition education or a control group receiving standard antenatal care. Maternal anthropometry, hemoglobin, calcium, and protein intake were assessed at baseline and in the third trimester, and maternal biomarkers at delivery and birth outcomes were analysed using regression methods. Results: Of 200 women, 173 (88 in the intervention group, 85 in the control group) completed follow-up. At baseline, 45.7% were anemic; after the intervention, normal hemoglobin levels rose to 73.9% in the intervention group, compared with 35.3% in the control group. Hypocalcemia at delivery was 1.1% in the intervention group compared with 22.4% in controls. Protein intake and BMI improved significantly with education. Hemoglobin and calcium at birth were positively correlated in the intervention group (r=0.372, p<0.05), but not in the control group. Neonatal birthweight was marginally higher, and low birthweight was less frequent in the intervention group, though the differences were not statistically significant. Conclusions: Trimester-specific nutrition education substantially improved maternal hemoglobin levels, calcium status, and dietary practices and is feasible for integration into routine antenatal care to support better perinatal outcomes in India.